DEVELOPING THE OPPORTUNITIES OF FORMING STUDENTS' ECOLOGICAL THINKING IN THE TEACHING OF NATURAL SCIENCES (World Bulletin of Social Sciences, 2024)
The article examines the development of opportunities for the formation of environmental thinking in students when teaching natural science in primary school. Attention is focused on developing students' environmental thinking that a love of nature will make them realize that water is an invaluable resource.
Keywords: Ecological education; educational technologies; natural science